2015
DOI: 10.1007/978-3-319-17121-0_87
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Arf-like Proteins ARL2 and ARL3 in Photoreceptors

Abstract: Arf-like proteins (ARLs) are ubiquitously expressed small G proteins of the RAS superfamily. In photoreceptors, ARL2 and ARL3 participate in the trafficking of lipidated membrane-associated proteins and colocalize in the inner segment with UNC119A and PDEδ. UNC119A and PDEδ are acyl- and prenyl-binding proteins, respectively, involved in trafficking of acylated (transducin-α subunit, nephrocystin NPHP3) and prenylated proteins (GRK1, PDE6). Germline Arl3 knockout mice do not survive beyond postnatal day 21 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Arl3 appears to be essential for cilia function as deletion leads to widespread ciliopathy and high levels of embryonic lethality ( 30 , 55 , 56 ). Arl3 function is regulated through its GAP RP2 and GEF Arl13b.…”
Section: Discussionmentioning
confidence: 99%
“…Arl3 appears to be essential for cilia function as deletion leads to widespread ciliopathy and high levels of embryonic lethality ( 30 , 55 , 56 ). Arl3 function is regulated through its GAP RP2 and GEF Arl13b.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study has shown that regulation of Arf signaling reverses mutant protein toxicity in ALS by decreasing ER stress and stimulating various types of autophagy in cell lines and animal models (Zhai et al, 2015). Recent studies have shown that Arl proteins which belong to Arf GTPases are associated with retinitis pigmentosa (Veltel et al, 2008a; Zhang H. et al, 2015; Hanke-Gogokhia et al, 2016b). In the pathogenetic process of retinitis pigmentosa, Arl2/Arl3 signaling plays important roles in photoreceptor function by regulating lipid-modified membrane-associated proteins (Hanke-Gogokhia et al, 2016b).…”
Section: The Arf Subfamily In Non-neoplastic Cerebral Diseasesmentioning
confidence: 99%
“…Recent studies have shown that Arl proteins which belong to Arf GTPases are associated with retinitis pigmentosa (Veltel et al, 2008a; Zhang H. et al, 2015; Hanke-Gogokhia et al, 2016b). In the pathogenetic process of retinitis pigmentosa, Arl2/Arl3 signaling plays important roles in photoreceptor function by regulating lipid-modified membrane-associated proteins (Hanke-Gogokhia et al, 2016b). The formation of a ternary complex between Arl3, its cognate GAP RP2 and its retinal effector HRG4 is also of great importance for photoreceptor function (Veltel et al, 2008b).…”
Section: The Arf Subfamily In Non-neoplastic Cerebral Diseasesmentioning
confidence: 99%
“…Both RP2 and Arl3 localize to the connecting cilium of photoreceptors (Grayson et al, 2002). Arl3 has been linked to the trafficking of lipidated membrane-associated proteins (Hanke-Gogokhia et al, 2016a; Hanke-Gogokhia et al, 2016b). Defects Arl3-mediated trafficking of prenylated proteins in rod photoreceptors led to cell death and retinal degeneration (Wright et al, 2016) Although human mutations in ARL3 have not yet been identified, the Arl3 −/− knockout mice exhibit phenotypes consistent with ciliary defects (Schrick et al, 2006).…”
Section: Introductionmentioning
confidence: 99%